Comparison between 5-azacytidine treatment and allogeneic stem-cell transplantation in elderly patients with advanced MDS according to donor availability (VidazaAllo Study) - Kröger, Nicolaus; Sockel, Katja; Wolschke, Christine; Bethge, Wolfgang; Schlenk, Richard Friedrich; Wolf, Dominik; Stadler, Michael; Kobbe, Guido; Wulf, Gerald; Bug, Gesine; Schäfer-Eckart, Kerstin; Scheid, Christof; et al. (Journal of clinical oncology, 2021)
PURPOSE - - In contrast to 5-azacytidine (5-aza), allogeneic stem-cell transplantation (HSCT) represents a curative treatment strategy for patients with myelodysplastic syndromes (MDS), but therapy-related mortality (TRM) limits its broader use in elderly patients with MDS. The present prospective multicenter study compared HSCT following 5-aza pretreatment with continuous 5-aza treatment in patients with higher-risk MDS age 55-70 years. - - METHODS - - One hundred ninety patients with a median age of 63 years were enrolled. Patients received 4-6 cycles of 5-aza followed by HLA-compatible HSCT after reduced-intensity conditioning or by continuous 5-aza if no donor was identified. - - RESULTS - - Twenty-eight patients did not fulfill inclusion criteria (n = 20), died (n = 2) withdrew informed consent (n = 5), or were excluded for an unknown reason (n = 1). 5-aza induction started in 162 patients, but only 108 (67%) were eligible for subsequent allocation to HSCT (n = 81) or continuation of 5-aza (n = 27) because of disease progression (n = 26), death (n = 12), or other reasons (n = 16). Seven percent died during 5-aza before treatment allocation. The cumulative incidence of TRM after HSCT at 1 year was 19%. The event-free survival and overall survival after 5-aza pretreatment and treatment allocation at 3 years were 34% (95% CI, 22 to 47) and 50% (95% CI, 39 to 61) after allograft and 0% and 32% (95% CI, 14 to 52) after continuous 5-aza treatment (P < .0001 and P = .12), respectively. Fourteen patients progressing after continuous 5-aza received a salvage allograft from an alternative donor, and 43% were alive at last follow-up. - - CONCLUSION - - In older patients with MDS, reduced-intensity conditioning HSCT resulted in a significantly improved event-free survival in comparison with continuous 5-aza therapy. Bridging with 5-aza to HSCT before is associated with a considerable rate of dropouts because of progression, mortality, and adverse events.